The postmodern mythology of Michel Tournier - Panek, Melissa Barchi (Cambridge Scholars, 2012)
"Michel Tournier defines the supreme mission of a writer to be the creation of a mythology which allows for interaction with his readers, who seem to be losing their critical faculties in our contemporary, postmodern world dominated by consumption and dizzying technological advances. Our contemporary society has changed due to the end of the modern era with its reigning ideologies. Collapsing after the atrocities of the Second World War, Modernity and the artistic and literary reactions referred to as modernism, have likewise been transformed. Myth continues to represent the collectivity of human existence, yet, in the short stories and novels of Michel Tournier, myth represents the collapse of the all-encompasing ideologies inherent to the Modern era. The grand narrative of Modernity such as Christianity and Man's reason have been deconstructed in the postmodern era. The mythology of Michel Tournier expresses these trends towards the dissolution of Modernity and creates individual, mini narratives which emphasize the particularity of individual existence.